Surface velocity and mass balance of Livingston Island ice cap, Antarctica - Osmanoglu, Batuhan; Navarro Valero, Francisco José; Hock, Regine; Braun, M.; Corcuera Labrado, María Isabel (The Cryosphere, 2014)
The mass budget of the ice caps surrounding the Antarctica Peninsula and, in particular, the partitioning of its main components are poorly known. Here we approximate frontal ablation (i.e. the sum of mass losses by calving and submarine melt) and surface mass balance of the ice cap of Livingston Island, the second largest island in the South Shetland Islands archipelago, and analyse variations in surface velocity for the period 2007–2011. Velocities are obtained from feature tracking using 25 PALSAR-1 images, and used in conjunction with estimates of glacier ice thicknesses inferred from principles of glacier dynamics and ground-penetrating radar observations to estimate frontal ablation rates by a flux-gate approach. Glacier-wide surface mass-balance rates are approximated from in situ observations on two glaciers of the ice cap. Within the limitations of the large uncertainties mostly due to unknown ice thicknesses at the flux gates, we find that frontal ablation (−509 ± 263 Mt yr−1, equivalent to −0.73 ± 0.38 m w.e. yr−1 over the ice cap area of 697 km2) and surface ablation (−0.73 ± 0.10 m w.e. yr−1) contribute similar shares to total ablation (−1.46 ± 0.39 m w.e. yr−1). Total mass change (δM = −0.67 ± 0.40 m w.e. yr−1) is negative despite a slightly positive surface mass balance (0.06 ± 0.14 m w.e. yr−1). We find large interannual and, for some basins, pronounced seasonal variations in surface velocities at the flux gates, with higher velocities in summer than in winter. Associated variations in frontal ablation (of ~237 Mt yr−1; −0.34 m w.e. yr−1) highlight the importance of taking into account the seasonality in ice velocities when computing frontal ablation with a flux-gate approach.